ANALYSIS OF THE FINANCIAL POSITION OF MILL COMPANIES IN VOJVODINA - Tekić, Dragana (Journal on Processing and Energy in Agriculture, 2021)
The subject of this research is the financial position of mill companies in Vojvodina. The specific aim of the research is to analyzed the financial position, ie to assess the risk of bankruptcy of medium-sized mill companies in Vojvodina. The general aim of the research is to compare the applied models for the analysis of financial position. The basis of the analysis are the financial reports of the observed companies in the period from 2015 to 2019. The analysis of financial position was performed using two models: Altman's Z-score model and Kralicek's Quick test model. These models use standard financial ratio indicators to assess the risk of bankruptcy of companies, ie their financial stability and profitability. The obtained results suggest that the company MLINTEST stood out as the most successful company, and that the company KIKINDSKI MLIN stood out as the company with the worst financial position. Both models gave similar results, and their further use is recommended when analyzing the financial position of mill companies in Vojvodina.
Keywords: Altman Z-score, Kralicek's Quick test, mill companies, bankruptcy